Sustainable Enterprise Resource Planning (S-ERP) for Industry 4. 0 : A Secure and Ethical Deployment Approach. - Anjaria, Kushal (Contributions to Management Science Series, 2025)
This book delves into integrating sustainable practices within enterprise resource planning (S-ERP) systems framework, particularly in the context of Industry 4.0.It offers a comprehensive exploration of how S-ERP systems can be developed and implemented to enhance operational efficiency and promote environmental and social sustainability, which.